Efficacy and safety of D-TACE followed by D-RFA for unresectable large hepatocellular carcinoma - Pang, Qingqing; Luo, Wenping; Chen, Shaojun; Zhou, Hua; Zhang, Riguang; Li, Yueyong; Zhao, Jianbo; Yuan, Chunwang; Wang, Guodong (Frontiers in Oncology, 2025)
ObjectiveTo evaluate the safety and short-term clinical efficacy of drug-loaded polyvinyl alcohol microspheres transarterial chemoembolization (D-TACE) in the treatment of unresectable large liver carcinoma with sequential double-needle water-cooled circulating radiofrequency ablation (D-RFA).MethodsA retrospective analysis was performed for patients with large hepatocellular carcinoma who underwent sequential D-TACE with D-RFA treatment at our hospital. From May 2019 to May 2023, a total of 143 intrahepatic malignant lesions were treated, and a total of 110 D-TACE and 96 D-RFA interventional therapy procedures were performed. The short-term efficacy at 1, 3, and 6 months after interventional therapy was analyzed based on the modified Response Evaluation Criteria in Solid Tumor (2020 edition) criteria. The evaluation included the efficacy of local tumor control, feasibility of technical implementation, safety of surgery, and tolerability by surgical patients.ResultsSixty-two patients underwent successful interventional therapy, achieving good technical feasibility. The objective response rate (ORR) at 3, 6, and 12 months was 90.4%, 85.5%, and 74.2%, respectively. The median overall survival (OS) was 35.0 months (95% CI: 24.7-45.3). The survival rates at 3, 6, and 12 months were 100% (62/62), 96.7% (60/62), and 93.5% (58/62), respectively. No cases of death occurred due to serious complications such as ectopic embolism, tumor rupture, or liver failure within 1 month after surgery. Two cases of postoperative tumor lysis syndrome, 3 cases of pleural effusion caused by intercostal artery injury, and 4 cases of small effusion in the abdominal cavity were reported. Eight cases of mild, moderate, and severe abdominal pain during or after the operation; 6 cases had mild to moderate liver function impairment. Eight patients experienced fever within 1 week after surgery.ConclusionThe D-TACE with sequential D-RFA technique for the treatment of unresectable large liver cancer is safe and controllable, with a high ORR. This combination treatment provides a useful reference value for the exploration of new treatment modes for advanced liver cancer, but the long-term efficacy evaluation requires multi-center, large-sample clinical studies, and continuous follow-up data analysis.